Traumatic extensor tendons injuries of the foot in childhood: a case report - Pedrazzini, Alessio; Valenti, Pier Giulio; Bertoni, Nicola; Pedrabissi, Bianca; Simo, Henry Yewo; Bisaschi, Roberto; Medina, Vanni; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Extensor tendon injuries of the foot in children represent a rare foot injury. We report a case of a 9 year-old male who suffered of a traumatic wound laceration in the distal third of the right leg with a glass the day before in another country, getting a combined injury of tibialis anterior (TA), extensor hallucis longus (EHL) and extensor digitorum longus (EDL). Methods: After an initial clinical and radiological evaluation, antibiotic prophylaxis was immediately started. Surgery was necessary for the repair of the lesions and after rehabilitation the patient recovered a good function with a complete return to a normal life. Results: 5 years follow-up clinical examination revealed a complete and painless range of movement comparable to the other foot. The patient regained active dorsiflexion without functional limitations, deformity or contracture. Conclusions: Early exploration is important to allow full definition of the extent of injury and early surgical repair of tendons is recommended to avoid future disability.